Straight Tube Corner Fill of Aluminum Alloys Tubes: Experiments and Fe Analysis - J. Gholipour; M. J. Worswick; C. Hari Manoj Simha (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Due to the high pressures involved in the hydroforming process, friction and lubrication play an important role and can affect formability of the material. Tubes of A1Mg3.5Mn aluminum alloy, of 76.2 mm (3 inch) outside diameter and 2-mm thickness were considered in this study. Three kinds of lubricants, Al070, Hydrodraw711 and water, were applied to the tubes and tubes were hydroformed to burst in a square shape die cavity. The key process parameters were recorded during the tests. An in-house Gurson-Tvergaard-Needleman (GTN) damage-based material model, implemented in LS-DYNA, was used to model the process and predict the formability of this material. The applied axial loads and internal pressures recorded during the tests were used in the computations. The effect of different types of elements (solid and shell) with different constitutive models (von Mises and GTN models) in predicting the strain distribution is studied. The GTN damage-based material showed a good ability to capture necking and displacement histories in this process. Both predicted and measured results showed that the lubricant with lower coefficient of friction can effectively increase the comer expansion.